Complete or partial reduction of the Met receptor tyrosine kinase in distinct circuits differentially impacts mouse behavior. Issue 1 (December 2015) - Thompson, Barbara; Levitt, Pat
Abstract Background Our laboratory discovered that the gene encoding the receptor tyrosine kinase, MET, contributes to autism risk. Expression ofMET is reduced in human postmortem temporal lobe in autism and Rett Syndrome. Subsequent studies revealed a role forMET in human and mouse functional and structural cortical connectivity. To further understand the contribution of Met to brain development and its impact on behavior, we generated two conditional mouse lines in whichMet is deleted from select populations of central nervous system neurons. Mice were then tested to determine the consequences of disruptingMet expression. Methods Mating ofEmx1 cre andMet fx /fx mice eliminates receptor signaling from all cells arising from the dorsal pallium.Met fx /fx andNestin cre crosses result in receptor signaling elimination from all neural cells. Behavioral tests were performed to assess cognitive, emotional, and social impairments that are observed in multiple neurodevelopmental disorders and that are in part subserved by circuits that express Met. Results Met fx /fx /Emx1 cre null mice displayed significant hypoactivity in the activity chamber and in the T-maze despite superior performance on the rotarod. Additionally, these animals showed a deficit in spontaneous alternation. Surprisingly, Met fx /fx; fx /+ /Nestin cre null and heterozygous mice exhibited deficits in contextual fear conditioning, andMet fx /+ /Nestin cre heterozygous mice spent less time in the closed arms of the elevated plus maze. Conclusions These data suggest a complex contribution of Met in the development of circuits mediating social, emotional, and cognitive behavior. The impact of disrupting developmental Met expression is dependent upon circuit-specific deletion patterns and levels of receptor activity.